LENGTH-WEIGHT RELATIONSHIP, RELATIVE CONDITION FACTOR, FOOD AND FEEDING HABITS OF CHANNA STRIATA FROM WETLANDS OF NADIA DISTRICT, WEST BENGAL - CHAKRABORTY, RUPALI; DAS, SUDHIR KUMAR; BHAKTA, DIBAKAR (Journal of the Inland Fisheries Society of India, 2021)
Samples of 226 numbers of Channa striata were examined during October, 2003 to May, 2004 to find out length-weight relationships, relative condition factor and food and feeding habits. Total length of the fish sample ranged from 130-400 mm and weight 65-955 g. The species was categorized into two group's viz., Group I (< 200 mm) and Group II ( 200 mm) for convenience of interpretation. The length weight relationship was recorded as W = 0.0072 L3.104 for the Group I and W = 0.0068 L3.060 for Group II. The 'b' value was recorded as 3.104 and 3.060 for the Group I and Group II specimens respectively. The growth of the fish was found to be isometric because 'b' value was not significantly different (P